Internet connectivity disruption in Jordan (Jordan) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Jordan. Data sourced from IODA.
Network Disruption Incident ID: JO-2026-0220. Severity: critical. Confidence: 67%